Pelatihan Bertanam Sayuran dengan Teknik Vertikultur pada Paguyuban Wali Murid Raudhotul Athfal Thoriqul Falah - Dede Nuraida; Tabitha Sri Hartati Wulandari; Supiana Dian Nurtjahyani; Sulistiono (Jurnal Pemberdayaan Masyarakat, 2023)
Raudhotul Athfal (RA) Thoriqul Falah is located in Talang Kembar Village. Mothers in Talang Kembar Village are generally unproductive housewives, so there needs to be empowerment to be more productive. The purpose of this training is to provide skills for the parents of the RA Thoriqul Falah Student, in making gardening places using vertical culture, making media, as well as selecting and planting seeds. This training activity is carried out in 2 methods, namely socialization about verticulture, and practice. The socialization method was carried out in the RA meeting room, while the practice was carried out in the school yard. The vertical planting is made from used mineral water bottles and paralon. The vegetables used were lettuce, pokcoy, and celery grown in a mixture of soil, husk and manure in a ratio of 2:1:1. Questionnaire given to all participants to find out the participants' interest in applying this technique. The results of this training showed that all participants were able to make vertical planting. All participants were able to make a composition of planting media, and were able to select and plant seeds. The results of the questionnaire showed that 90% of the participants were interested in applying this technique.